ANALISIS PELAKSANAAN PROBITY AUDIT PENGADAAN BARANG/JASA PEMERINTAH PADA INSPEKTORAT DAERAH PROVINSI SULAWESI UTARA - Jusuf, Renaldo Andrew; Nangoi, Grace B.; Tinangon, Jantje J. (Universitas Sam Ratulangi, 2021)
Government goods/services procurement is the mechanism of government spending that absorbs the most budget. According to LKPP, every year the procurement of goods/services absorbs a budget of around 40% of the APBN and APBD. Due to the large budget in the procurement of goods/services so the possibility of deviation is very large. One of the Government's efforts to prevent fraud is to implement a new type of audit, the probity audit of goods/services procurement. But seeing the current conditions that there are still many cases of corruption in the procurement of goods / services even though a probity audit has been applied, it indicates that the probity audit carried out does not meet the expected objectives. This study aimed to find out what are the problems in implementing a probity audit and the steps that must be taken to overcome the problems that arise in the conduct of a probity audit. This study uses a qualitative method with a case study approach to the Regional Inspectorate of North Sulawesi Province. The Regional Inspectorate of North Sulawesi Province was chosen because it has conducted a probity audit from 2015 to 2019. The informants in this study were functional officials (Auditors and P2UPD) who carried out probity audits, starting from the level of Team Members, Team Leaders and Technical Controllers. The results of the study found that there were still many problems in implementing the probity audit by the Regional Inspectorate of North Sulawesi Province. Problems exist at each stage of the probity audit, starting from the preparation stage to the follow-up stages of the results of the audit, among others there are no internal policies related to the implementation of the audit probity, in house training has not been carried out optimally, the implementation of the audit probity is not real time and is only carried out once a year, there is still a lack of auditors who are competent in goods / services audits, audits do not have enough time, physical audits and market price comparisons are not carried out and correction action to the problem found of probity audits is not carried out.